TATANIAGA DAN MARGIN PEMASARAN IKAN TUNA DI KOTA GORONTALO - Lis M Yapanto (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2020)
This study aims to determine the marketing of tuna fish in the city of Gorontalo. The analysis used includes marketing margin analysis, profit analysis, marketing efficiency analysis. The study was conducted in October-December 2019 in Gorontalo City. Tuna marketing institutions include; retailers, traveling vendors, and collectors. Tuna fish marketing in Gorontalo City follows general marketing channels, institutions that carry out marketing activities or functions from the producers to the consumers. Tuna Fish marketing is done alone by fishermen or through retailers, traveling traders and (local) collectors, and then sold directly to consumers. Fishermen sell to the market, limited to retailers and direct consumers, with marketing areas only for traditional markets in the city of Gorontalo. Fishermen sell fish to big traders, then big traders sell Tuna fish to exporters in Bali, Makassar, Palu and Surabaya. Exporters then export tuna fish to foreign countries. The initial price of tuna from producers (fishermen) is IDR 40,000 / kg based on the results of an analysis that shows that the margins of each marketing institution include retailers IDR 20,000 / kg, traveling traders IDR 30,000 / kg and traders gathering IDR 50,000 / kg . The highest margin is the trader 55.56%.